EFFICACY EVALUATION OF BD ORAL SPRAY ON THE SYMPTOMS AND COURSE OF COVID-19 PATIENTS IN THE CLINICAL HOSPITAL - Pham Van Hung; Nguyen Huy Binh; Tran Hong Tram; Phung Lam Toi (JOURNAL OF CONTROL VACCINES AND BIOLOGICALS, 2023)
A prospective randomized, open-label, single-blinded clinical trial was conducted to evaluate the efficacy of BD on the symptoms and course of the disease in patients with moderate and severe Covid-19 in the field hospital. 200 hospitalized patients with Covid-19 diagnosis were enrolled. The patients were randomized into 100 patients in the interventional group (BD group) and 100 in the control group. The BD group patients were treated with BD oral spray in conjunction with standard Covid-19 treatment protocol. The control group patients were treated with standard of care without BD. Patients of the BD group demonstrated a significantly faster improvement in all Covid-19 related symptoms, resulting in a shorter time for complete recovery than the control group. More remarkably, patients in the BD group showed a shorter time for complete viral clearance. The addition of BD to the standard of care protocol also resulted in significant improvement in the restoration of taste and smell and reduction of lung infiltration. The patients in the BD group also exhibited fewer adverse events related to treatment. BD is a simple-to-use, safe, and effective adjunctive treatment for moderate and severe Covid-19 cases. BD might be effective for Covid-19 symptoms.